Comparative long-term outcomes of unicompartmental and total knee arthroplasty in knee osteoarthritis patients: a systematic review and meta-analysis - Hu, Hai; Li, Pengfei; Liu, Zelin; Lv, Hang; Yang, Xiangjun; Liu, Peiran (Frontiers in Surgery, 2024)
Background Long-term outcomes for knee osteoarthritis patients undergoing unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) remain inconclusive. Objectives This study aims to evaluate the long-term outcomes over five years, including Knee Society Pain Scores (KSPS), Knee Society Scores (KSS), Knee Society Function Scores (KSFS), range of motion (ROM), and survival rates—of UKA versus TKA in knee osteoarthritis patients. Design Systematic review using data from randomized controlled and cohort trials, and world databases. Data sources Researchers searched Medline, Embase, Cochrane Controlled Register of Trials, and Clinical Trials.gov from January 1990 to March 2024. Eligibility criteria for selecting studies The researchers selected studies based on adult participants with knee osteoarthritis. Eligible studies compare UKA and TKA reports on clinical or surgical outcomes, including KSPS, KSS, KSFS, ROM and survival rates, over 5 years. The researchers excluded the studies fewer than five years, or if English text was unavailable. Results Researchers categorized twenty-nine eligible studies into three groups: five randomized controlled trials, 11 registries and database studies, and 13 cohort studies. The analysis revealed that neither TKA nor UKA definitively outperformed the other in terms of pain (SMD (95% CI): -0.06[-0.41, 0.28], I2=90%) and KSS scores (SMD (95% CI): -0.07[-0.23, 0.008], I2=81%) over a period of five years. However, KSFS (SMD (95% CI): -0.30[-0.43, -0.17], I2=74%) and ROM (SMD (95% CI): -0.78[-1.11, -0.46], I2=92%) tended to favor UKA, and survival rate favor TKA at 5 or over 5-year follow-up periods. Conclusions UKA shows a trend towards better outcomes in KSFS and ROM, alongside a more favorable survival rate in TKA at the five-year and beyond follow-up periods.